2021
DOI: 10.1080/10872981.2021.1919042
|View full text |Cite
|
Sign up to set email alerts
|

Perception of medical education by learners and teachers during the COVID-19 pandemic: a cross-sectional survey of online teaching

Abstract: COVID-19 lockdowns have deeply impacted teaching programs. Online teaching has suddenly become the main form of medical education, a form that may be used as long as the pandemic continues. We aimed at analyzing how online teaching was perceived by both teachers and learners to help determine how to adapt curricula in the next few years. An anonymous cross-sectional survey of medical students, pediatric residents, neonatal fellows, and their respective teachers was conducted between June and August 2020 to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 37 publications
2
49
2
1
Order By: Relevance
“…However, as the literature suggests, while learners report preferences regarding their learning styles, they also tend to adapt their learning to the available teaching strategies, based on the context and motivations (Entwistle, 1997). Recently, Motte-Signoret et al (2021) indicated that both medical students and their instructors perceived e-learning as a suitable alternative medical education delivery method during the pandemic.…”
Section: Students' and Instructors' Complementarity In The Learning Processmentioning
confidence: 99%
“…However, as the literature suggests, while learners report preferences regarding their learning styles, they also tend to adapt their learning to the available teaching strategies, based on the context and motivations (Entwistle, 1997). Recently, Motte-Signoret et al (2021) indicated that both medical students and their instructors perceived e-learning as a suitable alternative medical education delivery method during the pandemic.…”
Section: Students' and Instructors' Complementarity In The Learning Processmentioning
confidence: 99%
“…In response to that, medical education has undergone changes and adjustments to maintain standards in medical education as well as minimize disruptions in knowledge training (Tabatabai, 2020). As an educational discipline that requires a lot of experimentation, medical education in the context of the COVID-19 crisis has highlighted the need to develop online learning and virtual education (Emmanuelle et al, 2021). For VR in the medical field, users have a visual impression of their experience.…”
Section: Virtual Medical With Medical Students In Online Educationmentioning
confidence: 99%
“…Since the end of 2019, COVID-19 has evolved into a pandemic [1] that made governments worldwide implement unprecedented non-pharmacological interventions in order to respond to the rapid spread of this new, life-threatening disease [4]. One of these measures, namely the enforcement of social Healthcare 2021, 9, 1141 2 of 8 distancing, resulted in fast transition from traditional teaching to digital teaching where feasible [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, educational institutions worldwide have faced a similar need for transition to digital teaching [5][6][7], while students, particularly in low-or middle-income countries, may encounter new or increasing barriers complicating educational access [11][12][13][14]. Maity et al [14] reported that university students, probably due to their overall higher maturity and commitment, appear to be less affected by the difficulties that arise from the pandemic-driven transition to digital education than students at school or at college.…”
Section: Introductionmentioning
confidence: 99%